IMPACT OF SPIRITUAL WELL-BEING ON MENTAL HEALTH AND BURNOUT AMONG DAIVA NARTHAKAS OF TULUNADU - Ms Ashwini H (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Spiritual well-being, mental health, and burnout are interrelated psychological variables that play a crucial role in the overall quality of life, particularly among individuals engaged in intense spiritual or ritualistic practices. Studying these variables among Daiva Narthakas, who perform traditional rituals of Daiva Aradhane in the culturally rich Tulunadu region, provides a unique chance to understand the psychological effects of spiritual involvement rooted in culture. These performers, often respected for their spiritual commitment, live a life focused on social responsibility, physical stamina, and deep spirituality. This lifestyle can affect their mental health in both beneficial and harmful ways. The aim of the study is to examine the impact of spiritual well-being on mental health and burnout among Daiva Narthakas. This study adopted a quantitative, cross-sectional research design. A total of 90 participants were selected through snowball and purposive sampling methods. Data were collected using standardized psychological scales: Spiritual Well-Being Scale (Paloutzian & Ellison, 1982), General Health Questionnaire (Goldberg & Hillier, 1979), and the Maslach Burnout Inventory (Maslach & Jackson, 1981). Normality tests indicated a mixed distribution, prompting the use of both non-parametric correlation (Spearman’s rho) and linear regression analyses. District-wise correlations revealed significant associations between spiritual well-being and general health in Dakshina Kannada and Udupi, while Kasaragod showed no significant relationships. Regression analysis indicated that spiritual well-being significantly predicted general health (R² = .234, p < .001) and burnout (R² = .079, p = .007) across the full sample. These findings highlight the protective role of spiritual well-being in promoting mental health and mitigating emotional exhaustion among ritual performers.